Implementation of the SP4N-LAPOR! Application Socialization in Managing Community Aspirations in Mekar Agung Village - Hartono, Hartono; Ulhaq, Abyan Dhiya; Nabilah, Hana; Agustin, Windi; Adinda, Vania Dwi; Prinawarni, Liani; Amin, Mohammad Nashrullah Al; Putri, Nurzihan Nabila; Farhan, Fandi; Nugraha, Gufron Suprijadi (Universitas Muhammadiyah Malang, 2026)
Community aspirations play an essential role in shaping the direction of public service development. The SP4N-LAPOR! application, designed under the No Wrong Door Policy, serves as a platform for channeling public complaints to authorized institutions. This study aims to analyze community readiness and legal culture in using SP4N-LAPOR!, evaluate the effectiveness of the socialization program, and identify obstacles in managing public complaints. Using a qualitative descriptive method through interviews, observations, and document analysis, the socialization in Mekar Agung Village increased public participation in reporting issues such as damaged roads, inadequate street lighting, and high stunting rates. However, limited digital literacy, weak legal awareness, and slow institutional response remain significant barriers. The findings align with public service and e-government theories, emphasizing the need for continuous monitoring, capacity building, and cross-sector collaboration to strengthen the effectiveness of public complaint management.